Glucose Sensing - Geddes, Chris D.; Lakowicz, Joseph R. (Topics in Fluorescence Spectroscopy, 2006)
Topics in Fluorescence Spectroscopy, Glucose Sensing is the eleventh volume in the popular series Topics in Fluorescence Spectroscopy, edited by Drs. Chris D. Geddes and Joseph R. Lakowicz. This volume incorporates authoritative analytical fluorescence-based glucose sensing reviews specialized enough to be attractive to professional researchers, yet also appealing to the wider audience of scientists in related disciplines of fluorescence. Glucose Sensing is an essential reference for any lab working in the analytical fluorescence glucose sensing field. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of glucose sensing, and diabetes care & management, will find this volume an invaluable resource. Topics in Fluorescence Spectroscopy Volume 11, Glucose Sensing Chapters include: Implantable Sensors for Interstitial Fluid Smart Tattoo Glucose Sensors Optical Enzyme-based Glucose Biosensors Plasmonic Glucose Sensing The Glucose Binding Protein for Sensing Fluorescent TICT Sensors for Saccharides Contact Lenses for Ophthalmic Glucose Monitoring About the Editors: Dr Chris D. Geddes is Professor of Fluorescence Spectroscopy, Director of the Institute of Fluorescence, and Associate Director of the Center for Fluorescence Spectroscopy at the University of Maryland Biotechnology Institute, Medical Biotechnology Center, Baltimore, USA. He is the Editor-in-Chief of the Journal of Fluorescence and both the Editor-in-Chief and Founding Editor of the Journal Plasmonics, The Who's Who in Fluorescence, Reviews in Fluorescence and Reviews in Plasmonics annual volumes, as well as Executive Director of the Society of Fluorescence. Dr Geddes has published over 120 scientific articles, papers, review articles, books and book chapters on the principles and applications of fluorescence. Dr Joseph R. Lakowicz is Professor of Biochemistry at the University of Maryland School of Medicine, Baltimore, and Director of the Center for Fluorescence Spectroscopy. Dr. Lakowicz has published over 400 scientific articles, has edited numerous books, holds 16 issued patents, and is the author of the widely used text Principles of Fluorescence Spectroscopy now in its 3rd edition. .